Risk Analysis of the Causes of Delay in Ship Construction (Case Study of KM CL 9E Ship Construction) - Gazali, Goldy Sandy; Baroroh, Intan (BERKALA SAINSTEK, 2022)
In shipbuilding work, the risk of delays must be analyzed and anticipated so that such delays do not occur and cause losses for both parties. This study aims to calculate the risk of a shipbuilding project using the Failure Mode and Effect Analysis (FMEA) method. The final result obtained is the result of the calculation of the Risk Priority Number (RPN) in determining what risks can af fect shipbuilding work. There are two jobs with RPN value > 200 which are classified as High Risk namely errors in lofting and damage to the pulley block as a supporting tool. The plans for risk management with the highest RPN value are then discussed with th e shipyard. Risk mitigation is carried out on the possible risk of errors in lofting, namely by adding worker personnel in the loft ing workshop who serve as supervisors and examiners. While the risk of breakage of the trough can be overcome by paying attention to the inventory and also the condition of the tool.